CLSI M100 performance standards for antimicrobial susceptibility testing. - Clinical and Laboratory Standards Institute ([Wayne, Pennsylvania] Clinical and Laboratory Standards Institute, 2025)
"The data in the tables are valid only if the methodologies in CLSI M02, M07, and M11 are followed. These standards contain information about disk diffusion (CLSI M02) and dilution (CLSI M07 and CLSI M11) test procedures for aerobic and anaerobic bacteria. Clinicians depend heavily on information from the microbiology laboratory for treating their seriously ill patients. The clinical importance of antimicrobial susceptibility test results demands that these tests be performed under optimal conditions and that laboratories have the capability to provide results for the newest antimicrobial agents. The tables presented in CLSI M100 represent the most current information for drug selection, interpretation, and quality control using the procedures standardized in CLSI M02, M07, and M11. Users should replace previously published tables with these new tables. Changes in the tables since the previous edition appear in boldface type."--
"A CLSI supplement for global application." -- Front cover
"CLSI M100 includes updated tables for the Clinical and Laboratory Standards Institute antimicrobial susceptibility testing standards CLSI M02. M07, and M11." -- Front cover
"January 2025"--Caption.
"Replaces CLSI M100-Ed34"--Caption.
Cover title.
Text parallel to spine.
Keywords: Laboratories -- Standards; Microbial sensitivity tests -- Standards; Microorganisms -- Effect of antibiotics on; Épreuves de sensibilité (Microbiologie) -- Normes; Laboratoires -- Normes; Micro-organismes -- Effets des antibiotiques sur